Study of the Relationship between Some Microorganism Isolated from Congenital Anomalies Neonatal Screening and Their Mothers in Iraqi Patient - alsaade, rayat (Iraqi National Journal of Nursing Specialties, 2017)
Objectives : This study was seeks to determine the IgG and IgM in serum mothers and their babies of Iraqi patient suffering from congenital anomalies toward some microorganisms such as Cytomegalovirus (CMV), Congenital toxoplasmosis , Congenital rubella and Genital herpes simplex virus (HSV) correlated with age and babies gender the sample was collected from AL- Alwayia hospital for children / Baghdad . Methodology : Fifth blood sample have been collected from mothers and their babies suffering from congenital anomalies to detection IgG and IgM of some viruses including as Cytomegalovirus (CMV), congenital toxoplasmosis , Congenital rubella and Genital herpes simplex virus (HSV) was diagnosed by , enzyme-linked immunosorbent assay ELISA . Results : This study was showed that 27 male and 23 female , the mother’s age was 18-33 years old while babies’ s age was 1 day – 18 months , the mean of this study was 24.46 with Std 4. 35 . The current study was noted the IgG of Congenital Toxoplasmosis in serum of mothers more than their infant at 37 , 20 (74 , 40 ) % respectively as positive result , also the highest frequency for the disease was IgG in mothers more than IgG in male babies of 19, 10 ( 70.37 , 37.04 ) respectively and 18 , 10 ( 78.26 , 43.48 ) respectively in female babies , also the high level of IgM of CMV in babies was 3 ( 6 %) (1 male and 2 female )of positive result distributed as IgM in mothers and baby at 3, 2 ( 11.11 , 8.7 )% respectively , on the other hand the IgM of HSV in babies was 3 (6% ) positive result 2 ( 7.41 %) positive result with male babies while 1 ( 4.35 %) with female baby. Finally the positive result of Rubella infection was with IgM babies at 3(6%) distributed the positive result was 2 (7.41%) in male babies and 1 ( 4.35 %) in female baby.